Impact of gender-norms on women’s economic resilience to climate change - Mudege, Netsayi Noris; Cole, Steven; Adeyeye, Olajumoke; Bullock, Renee; Achandi, Esther; Galiè, Alessandra; Muzungaire, Lizzy; Kakwasha, Keagan (CGIAR System Organization, 2024)
Research tools on the impact of gender norms on women’s economic resilience to climate change in order to develop gender transformative approaches to improve women’s resilience.